Visual Culture; Expanded Cinema and the Concept Of “Trisikon” as a Manifestation of Indonesia Cultural Diversity - Sito Fossy Biosa; Yasraf Amir Piliang; Hafiz Aziz Ahmad; Tisna Sanjaya (Advances In Social Humanities Research, 2026)
Visual culture understands cinematic practice not merely as aesthetic expression, but as a site of social meaning production shaped by the relationships between medium, space, and audience participation. Within this framework, expanded cinema opens new possibilities for experimental film practices that transcend conventional representational boundaries through multisensory and reflective experiences situated between reality, archive, and imagination. This research examines the concept of TRISIKON (three situations and conditions: live action, documentation–footage, and animation) as a cinematic creation model that manifests Indonesian cultural diversity through the dialectic of Chaos–Harmony, defined as the convergence of creative uncertainty and compositional order. Through a case study of the work Anemoia Utopia, Chaos–Harmony (cultural diversity) is interpreted not as a binary opposition but as a dynamic space reflecting relationships between humans, nature, and non-human entities within Indonesia’s plural cultural context. This study employs an art-based research methodology combined with a hermeneutic approach to interpret visual symbols, rhythms, and nonlinear narrative structures as intersections between aesthetic experience and social reality. The findings indicate that TRISIKON blurs the boundaries between documentation, performativity, and animation, transforming cinema into a participatory space that invites collective interpretation. Consequently, TRISIKON functions not only as an artistic method but also as an epistemological framework within visual culture studies, offering an understanding of cinema as a fluid and continually transforming cultural practice.